Limited predictive value of traditional comorbidities for readmission in acute decompensated heart failure - Gil Marcus; Antoinette Monayer; Gil Moravsky; Shmuel Fuchs; Avishay Grupper; Eran Kalmanovich; Sa’ar Minha (PLoS ONE, 2025)
Background Common comorbidities in heart failure (HF), including chronic kidney disease (CKD), diabetes mellitus (DM), ischemic heart disease (IHD), and atrial fibrillation, are frequently presumed to predict hospital readmission. However, recent studies have challenged their predictive strength, raising questions about their clinical utility for risk stratification. Methods We conducted a retrospective cohort study of 7,652 patients admitted with acute decompensated heart failure (ADHF) at a tertiary center between 2007 and 2017. Associations between comorbidities and readmission at 30 and 100 days were assessed using Fine-Gray competing risk models, with death as a competing event. Subdistribution hazard ratios (sHRs) were reported. Model performance was evaluated using receiver operating characteristic (ROC) analysis and area under the curve (AUC) values, assessing individual comorbidities and incremental combinations. All comorbidities were included irrespective of univariable significance, based on clinical relevance. Results Several comorbidities were significantly associated with readmission, including CKD (sHR 1.16–1.23), DM (sHR 1.18–1.27), IHD (sHR 1.10–1.15), and anemia (sHR 1.11). However, predictive power was poor. For 30-day readmission, AUC values ranged from 0.516 (COPD) to 0.529 (CKD), with a maximal AUC of 0.555 when combining the four strongest predictors. For 100-day readmission, AUC values ranged from 0.528 (DM) to 0.545 (CKD), with a maximal combined AUC of 0.593. Conclusions Despite consistent statistical associations, common comorbidities perform poorly as predictive tools for identifying individual patients at risk of HF readmission. These findings highlight the need for more robust risk models integrating dynamic clinical, laboratory, and patient-centered factors.